(untitled) (Research, Society and Development, 2023)
Eugenia uniflora L., belong to the Myrtaceae Family, is know by popular as pitanga (the fruit) and pitangueira, the tree. External and internal conditions are cited as interfering with the final content of secondary metabolites in medicinal plants.. The purpose of this research was to make a qualitative and quantitative phytochemical screening in different extracts of Eugenia uniflora L. The plant was was collected in Bagé/RS in February 2021. The qualitative phytochemical analysis was made thru the classic characterization reactions. For the quantitave analysis, three diferentes extracts were prepared: aqueous infusion, aqueous decoction and maceration in hydroalcoholic solvente (93%), all at 5% (w/v) concentration. The phenolic substances was determined by the Folin-Ciocalteau method and the flavanoids was determined per spectophotometry by the methodology described in the Brazilian Pharmacopoeia IV. In the qualitative evaluations we could verify a positive reaction for alkaloids, flavonoids, saponins and hydrolysable tannins. tannins and a negative reaction for cardiotonic glucosides. Among the tested extracts, the aqueous infusion showed lower values than the others in the determination of phenolic substances (5,91 µg/g; decoction 10,69 µg/g and maceration 10,02 µg/g) and flavonoids (0,47 mg/g; decoction 1,19 mg/g and maceration 2,59 mg/g) including with statistical variation. The results of this study infer the influence of internal (extraction method and solvents employed) and external factors in the production of secondary metabolities. It is believed that the presence of hydrolysable tannins may be related to the large volume of rainfall that occurred.